NEW REPRESENTATIVES OF THE GENERA GLOSSHYPOTHYRIDINA AND HYPOTHYRIDINA (RHYNCHONELLIDA) FROM THE DEVONIAN OF NOVAYA ZEMLYA - Tcherkesova S.V. (My University, 2002)
A new species, Glosshypothyridina chernogubensis sp. nov., from the Chernaya Bay Horizon (Givetian) and three new species Hypothyridina petrenkoi sp. nov., H. karnoushenkoi sp. nov., and H. harlovaensis sp. nov. from the Menshikov Horizon (Frasnian) are described. In the latter species, subspecies H. harlovaensis harlovaensis subsp. nov. and H. harlovaensis menshikovaensis subsp. nov. are recognized. A new subspecies Hypothyridina cuboides angusta subsp. nov. is described from the same horizon.
Keywords: Devonian; Paleozoic::Devonian; Палеозой::Девонская